2012
DOI: 10.1108/03699421211264848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of urethane acrylate from PENTA based polyol and EB curing with varying ratio of TMTPA

Abstract: Purpose -Urethane Acrylate Oligomer with 100% solids was synthesised and characterised in order to study the application in electron beam curing with varying ratio of Trimethylol propane triacrylate (TMPTA). The purpose of this paper is to study effect of TMPTA addition on the crosslink density and different coating properties. Design/methodology/approach -Polyester polyol was synthesised by reacting single diacid, adipic acid (AA), with Pentaerythritol (PENTA) and 1,6-hexanediol (HD). Further, Urethane acryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…There is a new peak at 29.60 ppm associated to new formed OCC (C10) after aza‐Michael addition, and another peak of new formed carbon CNC (C9) is overlapped with that of C8 leading to a broad peak at this area. It is worth pointing out that two weak but well‐defined signals are observed at 132.42 and 126.64 ppm, which are assigned to the CC group on acrylate of the TMPTA monomer 37,38 . The 13 C NMR results provide direct evidence for the presence of unreacted acrylate groups in the resultant PEA particles, which is in good agreement with the FTIR result.…”
Section: Resultssupporting
confidence: 83%
“…There is a new peak at 29.60 ppm associated to new formed OCC (C10) after aza‐Michael addition, and another peak of new formed carbon CNC (C9) is overlapped with that of C8 leading to a broad peak at this area. It is worth pointing out that two weak but well‐defined signals are observed at 132.42 and 126.64 ppm, which are assigned to the CC group on acrylate of the TMPTA monomer 37,38 . The 13 C NMR results provide direct evidence for the presence of unreacted acrylate groups in the resultant PEA particles, which is in good agreement with the FTIR result.…”
Section: Resultssupporting
confidence: 83%
“…The contact angle slightly increased with increasing SA content, possibly because (1) the CS amino groups were replaced by the hydrophobic SA moieties, which decreased the number of exposed hydrophilic groups, 45 and (2) the more compact structure held less water, which resulted in a lower swelling extent 46 . In addition, at the same SA content, cross‐linked films had higher water contact angles than non‐cross‐linked ones, which indicated that the composite OH groups were consumed via cross‐linking to afford denser and more compact surfaces 47 …”
Section: Resultsmentioning
confidence: 99%
“…46 In addition, at the same SA content, cross-linked films had higher water contact angles than non-cross-linked ones, which indicated that the composite OH groups were consumed via cross-linking to afford denser and more compact surfaces. 47 Figure 2b presents the solubility of CS, CS-g-SA (3), and MDI@CS-g-SA (3) films in various solvents arranged according to their polarity (left: high polarity, right: low polarity). The strong intra-molecular hydrogen bonding between the hydroxyl and amino groups of CS endows pure CS with a crystalline structure, and thus renders it poorly soluble in water and organic reagents.…”
Section: Hydrophobicity and Solubilitymentioning
confidence: 99%
“…The signal at 4.085 ppm referred to the CH 2 –O (C=O) proton, while the signal at 2.315 ppm referred to CH 2 –O (C=O). Due to protons CH 2 –CH 2 –O–(C=O), the signal at 1.62 ppm appears 30 . In the case of 1 H NMR of polyester from the glycolysis product of WPET, Fig.…”
Section: Resultsmentioning
confidence: 99%